Social Reconstruction as an Effort to Restorate the Concept of Educational Management - Indri, Indri (CV. Ulil Albab Corp, 2024)
Social reconstruction theory in the world of education emphasizes that education must act as a tool for social transformation that encourages students to think critically, understand social problems, and contribute to creating a more just and inclusive society. This article aims to explore more deeply the concept of social reconstruction theory in its urgency in the field of education management. This research uses a normative approach. The results of the study show that social reconstruction and educational management are interrelated in an effort to create an education system that is responsive to social change, where educational management functions as a tool for implementing strategies that support social transformation through inclusive and relevant learning.